Paints and varnishes. Determination of the percentage volume of non-volatile matter. Method using the determination of non-volatile-matter content in accordance with ISO 3251 and determination of dry film density on coated test panels by the Archimedes principle Part 2, (11th October 2019) - British Standards Institution,
No abstract available